2012
DOI: 10.1105/tpc.112.097105
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence Meristem Identity in Rice Is Specified by Overlapping Functions of Three AP1/FUL-Like MADS Box Genes and PAP2, a SEPALLATA MADS Box Gene

Abstract: In plants, the transition to reproductive growth is of particular importance for successful seed production. Transformation of the shoot apical meristem (SAM) to the inflorescence meristem (IM) is the crucial first step in this transition. Using laser microdissection and microarrays, we found that expression of PANICLE PHYTOMER2 (PAP2) and three APETALA1 (AP1)/ FRUITFULL (FUL)-like genes (MADS14, MADS15, and MADS18) is induced in the SAM during meristem phase transition in rice (Oryza sativa). PAP2 is a MADS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
270
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(285 citation statements)
references
References 51 publications
13
270
1
1
Order By: Relevance
“…OsMADS34 transcripts are at reduced levels in the young FM. In contrast, OsMADS1 transcripts are abundant in the incipient FM and nearly undetectable in empty glumes (Prasad et al, 2001;Gao et al, 2010;Kobayashi et al, 2010Kobayashi et al, , 2012. We found 4-fold increased transcript levels for OsMADS34 in PUbi: OsMADS1-DGR; P35S:OsMADS1amiR panicles (Fig.…”
Section: Loss-of-function Phenotypesmentioning
confidence: 74%
See 2 more Smart Citations
“…OsMADS34 transcripts are at reduced levels in the young FM. In contrast, OsMADS1 transcripts are abundant in the incipient FM and nearly undetectable in empty glumes (Prasad et al, 2001;Gao et al, 2010;Kobayashi et al, 2010Kobayashi et al, , 2012. We found 4-fold increased transcript levels for OsMADS34 in PUbi: OsMADS1-DGR; P35S:OsMADS1amiR panicles (Fig.…”
Section: Loss-of-function Phenotypesmentioning
confidence: 74%
“…But members of a grassspecific subgroup in the LOFSEP clade, OsMADS1, OsMADS5, and OsMADS34, have acquired novel functions (Malcomber and Kellogg, 2005;Gao et al, 2010;Kobayashi et al, 2010). OsMADS34 regulates panicle branching and promotes spikelet meristem and empty glume fate (Gao et al, 2010;Kobayashi et al, 2010Kobayashi et al, , 2012. OsMADS1 is expressed developmentally slightly later and is restricted to the incipient FM region of the spikelet and controls its fate (Jeon et al, 2000;Prasad et al, 2005).…”
Section: Osmads1 Is a Regulator Of Genetic Network That Control Thementioning
confidence: 99%
See 1 more Smart Citation
“…Other genes that show altered expression during early development but are not bound by the VRN1 protein might be indirectly regulated by increased activity of the VRN1 gene. For example, the expression of Barley MADS3, an APETALA-like (AP1) MADS box gene, is possibly activated by increased FT1 activity, since FT-like genes are known to activate the expression of AP1-like MADS box genes that play critical roles during later stages inflorescence development in cereal 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these programs are largely conserved across eudicots, we know little about how such mechanisms extend to grasses and/or to what extent novel factors have been recruited to pattern grass-specific inflorescence morphology. Some clues have emerged from expression profiling studies of grass inflorescence development, for example, in rice (Oryza sativa) (Furutani et al 2006;Kobayashi et al 2012). However, while homologs exist in other species, ra1 and ra3 themselves are found only within a clade known as the Panicoid grasses (Vollbrecht et al 2005;Doust 2007;Kellogg 2007), and it has been suggested that they function in a regulatory module that either was lost in other grass lineages or arose in Panicoids via subfunctionalization.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%